2023
DOI: 10.1177/24705470231156571
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Skin Conductance Reactivity to Stroke-Related Trauma Reminders During Hospitalization for Stroke

Abstract: Objective Although several risk factors for stroke-induced posttraumatic stress disorder (PTSD) have been identified, objective risk measures that can be detected in the acute aftermath of these events are needed. This study is the first to collect an objective measure of psychophysiological arousal—skin conductance (SC) reactivity to a trauma interview—in patients after stroke or transient ischemic attack (TIA) and investigate correlates of SC reactivity. Methods Mobile SC measurement during a resting baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…An inhospital study that used mobile assessments of SC reactivity measured during the acute aftermath of nonmedical trauma exposure found that heightened SC reactivity during a standardized trauma interview predicted subsequent development of PTSD symptoms and more chronic PTSD symptom manifestations [11]. Another recent study found that poststroke heightened SC was associated with several medically induced PTSD risk factors, including greater cumulative trauma burden and inhospital benzodiazepine administration [12]. Although SC measurement has traditionally been conducted in a research setting among individuals exposed to external (nonmedical) trauma, recently developed mobile SC assessments are a low-cost, noninvasive alternative, offering naturalistic measurement while patients are under the care of medical professionals following a serious medical event [11].…”
Section: Introductionmentioning
confidence: 99%
“…An inhospital study that used mobile assessments of SC reactivity measured during the acute aftermath of nonmedical trauma exposure found that heightened SC reactivity during a standardized trauma interview predicted subsequent development of PTSD symptoms and more chronic PTSD symptom manifestations [11]. Another recent study found that poststroke heightened SC was associated with several medically induced PTSD risk factors, including greater cumulative trauma burden and inhospital benzodiazepine administration [12]. Although SC measurement has traditionally been conducted in a research setting among individuals exposed to external (nonmedical) trauma, recently developed mobile SC assessments are a low-cost, noninvasive alternative, offering naturalistic measurement while patients are under the care of medical professionals following a serious medical event [11].…”
Section: Introductionmentioning
confidence: 99%